Hexakis{4-[(4′-hydroxybiphenyl-4-yl)ethynyl]phenyl}benzene - Silvia Valera; Bela E. Bode (Molbank, 2015)
A novel polyphenolic backbone, hexakis{4-[(4′-hydroxybiphenyl-4-yl)ethynyl]phenyl}benzene, was synthesised using a common synthetic protocol used for the synthesis of similar polyphenolic compounds.